Exposure to toxic substances and malignant tumors: condition and perspective in the Republic of Serbia - Živković-Perišić, Snežana (Archives of Pharmacy, 2022)
According to the latest estimates from the World Health Organization and the International Agency for Research on Cancer, number of malignant diseases worldwide has grown to 19.3 million and 9.9 million deaths have been registered in 2020. The aim of this work was to investigate public health importance of cancer burden due to exposure to carcinogens by conducting a review of professional journals and public health publications related  to toxic substances and emergence of malignant tumors. Increased cancer burden is a consequence of several factors, the most significant being total population growth and prolonged life expectancy, but also changes in cancer risk factors frequency, increasing exposure to known environmental carcinogens (chemicals, viruses and radiation), as well as adopting unhealthy lifestyles (smoking, alcohol intake, obesity and insufficient physical activity). Carcinogens are cancer-causing substances, damaging the genome or interrupting cell metabolic processes. Carcinogens typically have an "insidious" and not acute toxic effect and can be classified as genotoxic or non-genotoxic agents according to the mechanism of carcinogenesis. Genotoxins are directly attached to DNA, causing irreversible damage to the genome, such as polycyclic aromatic hydrocarbons. Non-genotoxic agents do not directly affect DNA, but can stimulate tumor growth, such as hormones and some organic compounds. In order to reduce exposure to known carcinogens, activities need to be conducted on multiple levels, primarily research, to better understand the mutual link between exposure and disease, implementation of existing regulations in health protection and implementation of legislation supporting public health and reducing malignant diseases burden.